Sepsis in cancer patients residing in Zimbabwe: spectrum of bacterial and fungal aetiologies and their antimicrobial susceptibility patterns - Chinowaita, Frank; Chaka, Wendy; Nyazika, Tinashe K.; Maboreke, Tendai C.; Tizauone, Emmanuel; Mapondera, Prichard; Chitsike, Inam; Cakana, Andrew Z.; Mavenyengwa, Rooyen T. (BioMed Central Ltd., 2021)
Background: Cancer and sepsis comorbidity is a major public health problem in most parts of the world including Zimbabwe. The microbial aetiologies of sepsis and their antibiograms vary with time and locations. Knowledge on local microbial aetiologies of sepsis and their susceptibility patterns is critical in guiding empirical antimicrobial treatment choices. Methods: This was a descriptive cross-sectional study which determined the microbial aetiologies of sepsis from blood cultures of paediatric and adult cancer patients obtained between July 2016 and June 2017. The TDR-X120 blood culture system and TDR 300B auto identification machine were used for incubation of blood culture bottles and identification plus antimicrobial susceptibility testing, respectively. Results: A total of 142 participants were enrolled; 50 (35.2%) had positive blood cultures, with 56.0% Gram positive,42.0% Gram-negative bacteria and 2.0% yeast isolated. Common species isolated included coagulase negative Staphylococcus spp. (CoNS) (22.0%), E. coli (16.0%), K. pneumoniae (14.0%), E. faecalis (14.0%) and S. aureus (8.0%). Gram-negative isolates exhibited high resistance to gentamicin (61.9%) and ceftriaxone (71.4%) which are the empiric antimicrobial agents used in our setting. Amikacin and meropenem showed 85.7 and 95.2% activity respectively against all Gram-negative isolates, whilst vancomycin and linezolid were effective against 96.2 and 100.0% of all Gram-positive isolates respectively. We isolated 10 (66.7%) extended spectrum β-lactamase (ESBL) amongst the E. coli and K. pneumoniae isolates. Ten (66.7%) of the Staphylococcus spp. were methicillin resistant. Conclusions: CoNS, E. coli, K. pneumoniae, E. faecalis and S. aureus were the major microbial drivers of sepsis amongst cancer patients in Zimbabwe. Most isolates were found to be resistant to commonly used empirical antibiotics, with isolates exhibiting high levels of ESBL and methicillin resistance carriage. A nationwide survey on microbial aetiologies of sepsis and their susceptibility patterns would assist in the guidance of effective sepsis empiric antimicrobial treatment among patients with cancer.